Green synthesis of silver nanoparticles via plant extracts: beginning a new era in cancer theranostics. (December 2016) - Ovais, Muhammad; Khalil, Ali Talha; Raza, Abida; Khan, Muhammad Adeeb; Ahmad, Irshad; Islam, Nazar Ul; Saravanan, Muthupandian; Ubaid, Muhammad Furqan; Ali, Muhammad; Shinwari, Zabta Khan
With the development of the latest technologies, scientists are looking to design novel strategies for the treatment and diagnosis of cancer. Advances in medicinal plant research and nanotechnology have attracted many researchers to the green synthesis of metallic nanoparticles due to its several advantages over conventional synthesis (simple, fast, energy efficient, one pot processes, safer, economical and biocompatibility). Medicinally active plants have proven to be the best reservoirs of diverse phytochemicals for the synthesis of biogenic silver nanoparticles (AgNPs). In this review, we discuss mechanistic advances in the synthesis and optimization of AgNPs from plant extracts. Moreover, we have thoroughly discussed the recent developments and milestones achieved in the use of biogenic AgNPs as cancer theranostic agents and their proposed mechanism of action. Anticipating all of the challenges, we hope that biogenic AgNPs may become a potential cancer theranostic agent in the near future.